VSe2 self-supporting structure electrode coated with ultrathin conformal PEDOT coating, and preparation method and application of VSe2 self-supporting structure electrode coated with ultrathin conformal PEDOT coating

Through the VSe2 self-supporting structure electrode covered with ultra-thin conformal PEDOT coating, the VSe2 nanosheets are solved in the capacity attenuation and manufacturing complexity of VSe2 nanosheets during lithium ion storage, achieving high conductivity and cyclic stability, suitable for magnesium lithium Hybrid batteries simplify process and reduce costs.

CN119297190AActive Publication Date: 2025-01-10WUHAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411446203.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-10
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the prior art, VSe2 nanosheets have volume changes, structural failure, slow ion diffusion kinetics and large strain during lithium ion storage, resulting in rapid capacity decay, and cumbersome manufacturing steps and high cost. The mechanical properties of the coating coating method Poor and difficult to control thickness.

Method used

The VSe2 self-supporting structure electrode coated with ultra-thin conformal PEDOT coating was prepared by vacuum suction filtration, and the VSe2 scales were grown by normal pressure chemical vapor deposition, and the PEDOT layer was coated by molecular layer deposition technology to simplify the process And achieve precise control of coating thickness.

Benefits of technology

A VSe2 electrode with high conductivity and high specific capacity is realized, which alleviates mechanical degradation problems through PEDOT coating. It is suitable for magnesium-lithium hybrid batteries, improves electrochemical performance and cycle stability, and avoids high electronegative groups in the adhesive. Capture of intercalated ions reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297190A_ABST
    Figure CN119297190A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium-based battery electrode materials, in particular to a VSe2 self-supporting structure electrode coated with an ultrathin conformal PEDOT coating and a preparation method and application of the VSe2 self-supporting structure electrode coated with the ultrathin conformal PEDOT coating. Growing VSe2 scales through normal-pressure chemical vapor deposition; and repeatedly and alternately spraying and depositing an EDOT monomer and an oxidizing agent on the surface of the prepared integrated electrode in a pulse manner to obtain the VSe2 self-supporting structure integrated electrode coated with the PEDOT coating. The preparation method is simple and controllable. According to the present invention, the VSe2 of the 1T phase has the metal property, the conductivity can achieve 1000 S cm <-1 >, the strong electron transfer ability is provided, and the extra conductive agent is not required; the composite material has the characteristics of high conductivity and high specific capacity, and the problem of mechanical degradation caused by repeated intercalation and deintercalation of ions between layers is solved through coating of the PEDOT coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium-based battery electrode materials, and in particular to a VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating, and a preparation method and application thereof. Background Art

[0002] The demand for lithium-ion batteries has increased exponentially in recent years, driven by the growing markets for zero-emission electric vehicles, large-scale stationary storage for renewable energy production, and portable consumer electronics, and is expected to continue for at least the next few decades. However, the low natural abundance of lithium leads to an eventual shortage of lithium, and more seriously, safety concerns caused by lithium dendrites, so the development of new battery systems is crucial. Multivalent systems have shown potential as viable candidates to supplement future energy needs by adopting relatively safe metal anodes. Magnesium metal has a low reduction potential (-2.356 V vs. SHE) and a volumetric capacity of 3833 mAh cm -3 , the specific capacity is 2205mAh g -1 In particular, the natural abundance of magnesium in the earth's crust is as high as 2.3%, which makes rechargeable magnesium batteries advantageous in terms of production cost, and unlike lithium metal, magnesium has a weak tendency to dendrite, making rechargeable magnesium batteries inherently safer than lithium-ion batteries.

[0003] Despite the above advantages, the high charge density of Mg in rechargeable magnesium batteries 2+ It is very "bulky", so the traditional embedding method will become an obstacle to magnesium batteries, and there is also a serious lack of compatible positive electrode materials. These problems are huge obstacles on the road to practical application, which has prompted people to develop a dual-ion strategy, introduce active Li ions into the system, and use the advantages of the Mg negative electrode combined with the characteristics of rapid Li ion transmission to form a magnesium-lithium hybrid battery. This "series" method is a feasible way to promote the rapid kinetics of the positive electrode, bringing more possibilities for the effective matching of the Mg negative electrode with more practical positive electrodes.

[0004] Transition metal chalcogenides are one of the most popular families of two-dimensional layered materials with extensive research interests in electrochemical energy-related fields due to their fascinating properties. The metal atoms in each monolayer are sandwiched between two chalcogenides, resulting in a stoichiometric MX2, where M is a transition metal element and X is a chalcogen such as S, Se, or Te. Se belongs to the same family as S and has some similarities with S in some properties. However, Se exhibits better metallic and intrinsic electrical properties than S. Se has a higher electrical conductivity (10 -3 S m -1 ), exceeding S(5×10 -28 S m -1). Compared with transition metal sulfides, transition metal selenides (TMSes) exhibit excellent electrical conductivity, mechanical stability, thermal stability, and rich redox properties. 1T-VSe2 is a typical metallic member of the TMSes family. Its crystal structure is similar to layered graphite, and adjacent layers are stacked together through weak van der Waals interlayer interactions along the c-axis. Because it has a large interlayer spacing (-0.61nm), it is sufficient to achieve alkali metal ion intercalation; its high conductivity (≈1000S cm -1 ) can quickly transfer electrons during cycling, making it a promising candidate for future large-scale practical energy storage applications.

[0005] However, layered VSe2 has some challenging problems when storing guest ions, including slow kinetics and large strain of ion diffusion due to volume changes and structural damage during charge and discharge, resulting in rapid capacity decay. In current technology, preparing layered VSe2 nanomaterials, especially VSe2 nanosheets, is a solution. However, due to the van der Waals interaction between adjacent nanosheets, VSe2 nanosheets are easy to aggregate, thereby extending the diffusion distance of Li ions and reducing the storage active sites on the surface or edge of the layered VSe2. And one thing that cannot be ignored is that its manufacturing steps are cumbersome and the cost is extremely high. Prior art shows that coating the surface of electrode materials can effectively alleviate the problems of electrode mechanical failure and interface instability. Unfortunately, most coatings (carbon coatings, oxide coatings) have poor mechanical properties and cannot achieve precise control of coating thickness.

[0006] Therefore, it is crucial to develop a simple, fast and efficient method for preparing VSe2 electrodes and provide an electrode coating that can be precisely controlled to suppress mechanical failure problems. Summary of the invention

[0007] One of the purposes of the present invention is to provide a method for preparing a VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT (poly 3,4-ethylenedioxythiophene) coating, which is simple and controllable.

[0008] The second purpose of the present invention is to provide a VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating, which has high conductivity and high specific capacity, and solves the mechanical degradation problem caused by repeated ion insertion and deintercalation between layers through PEDOT coating, so that it is more suitable for the application of magnesium-lithium hybrid batteries.

[0009] The third object of the present invention is to provide an application of a VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating.

[0010] The solution adopted by the present invention to achieve one of the purposes is: a method for preparing a VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating, comprising the following steps:

[0011] S1: Preparation of carbon nanotube film current collector by vacuum filtration method: Multi-walled carbon nanotubes are added to a solvent and ultrasonically treated to obtain a fully dispersed multi-walled carbon nanotube suspension, and then vacuum filtered to obtain a carbon nanotube film sheet, which is then dried to obtain a carbon nanotube film current collector;

[0012] S2: VSe2 flakes grown by atmospheric pressure chemical vapor deposition: using a two-zone tubular furnace with separate temperature control, Se powder is placed in the upstream temperature zone, VCl3 powder is placed between the upstream and downstream temperature zones, and the carbon nanotube film current collector is placed downstream of the VCl3 powder. In an inert atmosphere with a certain amount of carrier gas, the upstream and downstream temperature zones are heated to 350-370°C and 600-650°C respectively and maintained for a certain period of time, followed by natural cooling, and finally a VSe2 integrated electrode directly grown on the surface of the carbon nanotube film current collector is obtained.

[0013] S3: Molecular layer deposition of PEDOT coating: On the surface of the integrated electrode prepared in step S2, EDOT monomer and oxidant are repeatedly and alternately pulse-sprayed and deposited to obtain a VSe2 self-supporting structure integrated electrode coated with a PEDOT coating.

[0014] Preferably, in step S1, the solvent is at least one of N-methylpyrrolidone, water and ethanol.

[0015] Preferably, in step S1, the concentration of the multi-walled carbon nanotubes in the solvent is 0.1-0.2 mg / mL.

[0016] Preferably, in step S1, the drying temperature is 80-120°C.

[0017] Preferably, in step S2, the mass ratio of VCl3 powder to Se powder is 1:5-10.

[0018] Preferably, in step S2, the carbon nanotube film current collector is placed 2-5 cm downstream of the VCl3 powder.

[0019] Preferably, step S2 also includes a cleaning process of the chamber, and the specific steps are: before heating, a mixed carrier gas of 95% N2+5% H2 with a flow rate of 200-300sccm is used for purging. At this time, the double temperature zone of the chamber is raised from room temperature to 120-150°C within 10 minutes, maintained for 20-30min, and then the carrier gas flow rate is reduced to 50-60sccm, and the temperature is raised for reaction, and the growth time is 10-30min.

[0020] By controlling the dosage of VCl3 and Se precursors and the growth time, the loading amount of the electrode active material can be directly regulated.

[0021] Preferably, in step S3, the oxidant is at least one of MoCl5, ReCl5, and SbCl5, the heating temperature of the oxidant is 180-200°C, the pulse pressure is 1-3Pa, the heating temperature of the EDOT monomer is 100-120°C, the pulse pressure is 5-10Pa., and the deposition temperature is 130-160°C.

[0022] Preferably, the deposition temperature is 150°C.

[0023] The amount of oxidant added is excessive.

[0024] The solution adopted by the present invention to achieve the second purpose is: a VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating is prepared by the method described.

[0025] The solution adopted by the present invention to achieve the third purpose is: the application of the VSe2 self-supporting structure electrode coated with the ultra-thin conformal PEDOT coating as the positive electrode material in the magnesium-lithium hybrid battery.

[0026] The specific steps of molecular layer deposition of PEDOT coating are: transferring the grown integrated electrode to the molecular layer deposition reaction chamber, heating to the deposition temperature, and heating the source bottle containing the oxidant and EDOT monomer to obtain sufficient vapor pressure, then pulse spraying EDOT monomer into the chamber, then purging with an inert carrier gas, then pulse spraying oxidant, and then purging with an inert carrier gas, and repeating this process until the deposition is completed to obtain a VSe2 self-supporting integrated electrode coated with a PEDOT coating. The inert carrier gas is nitrogen or argon. The heating temperatures of the oxidant and EDOT source bottle are 180-200°C and 100-120°C, respectively.

[0027] The present invention has the following advantages and beneficial effects:

[0028] The preparation method of the VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating of the present invention is simple and controllable, and only three steps are required from the current collector to the final electrode.

[0029] The preparation method of the present invention does not have any additional added components (conductive agent, binder), so there is no additional weight of inactive substances. The 1T phase VSe2 has metallic properties and the conductivity can reach 1000S cm -1 It has strong electron transfer ability without the need for additional conductive agents. In addition, it avoids certain highly electronegative groups in the binder from irreversibly capturing intercalated ions, resulting in an increase in irreversible capacity.

[0030] The VSe2 self-supporting structure electrode coated with the ultra-thin conformal PEDOT coating of the present invention has the characteristics of high conductivity and high specific capacity, and the mechanical degradation problem caused by repeated ion insertion and extraction between layers is solved by coating with the PEDOT coating. The PEDOT coating has high electronic ion conductivity and viscoelastic properties. This mechanical property can better adapt to the volume change of VSe2 during repeated ion insertion and extraction, relieve stress, and have a low molecular layer deposition temperature. Compared with the uneven coating and uncontrollable thickness of the commonly used solution method coating, the coating of the present invention is more uniform. The coating can control the thickness of the coating by the number of cycles of molecular layer deposition, and its precision control can reach the angstrom level, which is conducive to achieving excellent electrochemical performance.

[0031] The VSe2 self-supporting structure electrode coated with the ultra-thin conformal PEDOT coating of the present invention can be applied to magnesium-lithium hybrid batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a scanning electron microscope image of the VSe2 self-supporting structure electrode prepared by the present invention in Example 1;

[0033] Figure 2 is a scanning electron microscope image of the contact position between the bottom of the VSe2 nanosheet and the carbon nanotube film current collector in the VSe2 self-supporting structure electrode prepared by the present invention in Example 1;

[0034] Figure 3 is a scanning electron microscope image of the VSe2 self-supporting structure electrode prepared by the present invention in Example 1 after 10 cycles of molecular layer deposition;

[0035] Figure 4 is a transmission electron microscopy image of the VSe2 nanosheet prepared by the present invention in Example 1 after 10 cycles of molecular layer deposition;

[0036] Figure 5 is a transmission electron micrograph of the uncoated VSe2 nanosheet prepared by the present invention in Example 1;

[0037] Figure 6 It is the elemental EDS-mapping of the VSe2 nanosheets prepared by the present invention in Example 1 after 10 cycles of molecular layer deposition;

[0038] Figure 7 is the X-ray diffraction pattern of the VSe2 self-supporting structure electrode after 10 cycles of molecular layer deposition prepared by the present invention in Example 1 and without coating;

[0039] Figure 8 It is a constant current charge and discharge curve diagram of the molecular layer deposition prepared by the present invention in Example 1 after 10 cycles and the uncoated VSe2 self-supporting structure electrode used in a magnesium-lithium hybrid battery;

[0040] Fig. 9 It is a long cycle performance diagram of the VSe2 self-supporting structure electrode prepared by the present invention after 10 cycles of molecular layer deposition and uncoated at a current density of 1 A / g in Example 1;

[0041] Fig.10 It is a scanning electron microscope image of the molecular layer deposition prepared by the present invention in Example 1 after 10 cycles and the uncoated VSe2 self-supporting structure electrode after 500 cycles at a current density of 1 A / g.

[0042] Fig.11 is a transmission electron microscopy image of the VSe2 nanosheet prepared by the present invention in Example 2 after 20 cycles of molecular layer deposition;

[0043] Fig.12 It is a short cycle performance diagram of the molecular layer deposition prepared by the present invention in Example 2 after 20 cycles and the uncoated VSe2 self-supporting structure electrode at a current density of 200 mA / g;

[0044] Fig.13 The 5 mg / cm 2 Short-cycle performance of uncoated VSe2 free-standing structure electrode at 200 mA / g after 10 cycles of molecular layer deposition under high loading. DETAILED DESCRIPTION

[0045] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.

[0046] Example 1

[0047] S1: Preparation of carbon nanotube membrane current collector by vacuum filtration method: Pour 35 mg of multi-walled carbon nanotubes into 200 ml of N-methylpyrrolidone and ultrasonically treat for 6 hours to obtain a fully dispersed multi-walled carbon nanotube suspension, then vacuum filter to obtain a carbon nanotube membrane sheet, and finally put it in a forced air drying oven at 80°C and dry it for 24 hours to obtain a carbon nanotube membrane current collector.

[0048] S2: Growth of VSe2 nanosheets by atmospheric pressure chemical vapor deposition: Using a two-zone tubular furnace with separate temperature control, 0.1g of VCl3 powder, 0.5g of Se powder, and a carbon nanotube film current collector are placed on a quartz plate (boat). The Se powder is placed in the middle of the upstream temperature zone, the VCl3 powder is placed between the upstream and downstream temperature zones, and the carbon nanotube film current collector is placed ~2cm downstream of the VCl3. Before heating, a 95% N2+5% H2 mixed carrier gas is used for purging with a flow rate of 200-300sccm. At this time, the chamber double temperature zone is raised from room temperature to 120°C within 10 minutes and maintained for 20 minutes to create a preferred growth atmosphere. Then the carrier gas flow rate was reduced to 50 sccm. At the same time, the upstream and downstream temperature zones were heated to 370°C and 600°C at a heating rate of 5°C / min and 10°C / min, respectively, and maintained for 10 minutes. The furnace was then allowed to enter a natural cooling process, and finally a VSe2 integrated electrode directly grown on the carbon nanotube film current collector was obtained. Figure 1 As shown in the low-magnification scanning electron microscope (SEM) image of the vanadium diselenide nanosheet self-supporting electrode, the VSe2 nanosheets exhibit a tightly arranged vertical structure. This is because the dense carbon nanotubes are intertwined, providing a large specific surface area, increasing the VSe2 nucleation sites, and thus achieving the formation of a dense VSe2 nanosheet forest; further, through the local magnified SEM image of the nanosheet, it can be seen that the grown VSe2 nanosheets exhibit regular hexagonal or nearly hexagonal morphological features, indicating their high crystallinity and the nanosheets are interconnected. By examining the connection between the VSe2 nanosheet and the carbon nanotube film current collector, it was found that the bottom of the VSe2 nanosheet is embedded in the VSe2 ( Figure 2 ), forming a firm fit, enhancing mechanical connection stability and electrical contact.

[0049] S3: Molecular layer deposition of PEDOT coating: The grown electrode is transferred to the molecular layer deposition reaction chamber, the chamber is heated to 150°C, MoCl5 powder is used as the oxidant, EDOT is used as the reaction monomer, and is placed in a source bottle to supply the precursor. The temperatures of the two source bottles are maintained at 180°C and 100°C respectively, thereby maintaining the high vapor pressure of the two precursors to obtain a sufficient supply of precursors. The chamber's base pressure is ~600mtorr, using nitrogen as the carrier gas (150sccm). The cyclic process of molecular layer deposition of PEDOT includes ~1s EDOT pulse + ~100s nitrogen pulse + ~5s MoCl5 pulse + ~100s nitrogen pulse, and 10 cycles of deposition are performed. The morphology of the coated electrode was characterized by SEM ( Figure 3 ).and Figure 2In contrast, no obvious morphological changes were observed after PEDOT deposition, demonstrating the remarkable super-conformality of the molecular layer deposition technique. To further confirm the presence and uniformity of PEDOT, transmission electron microscopy observations and energy dispersive X-ray spectroscopy (EDS) elemental mapping analysis were performed on the coated VSe2 nanosheets. Figure 4 A uniform amorphous layer with a thickness of ∼5 nm was confirmed along the edges of the nanosheets. For comparison, uncoated VSe2 nanosheets were also characterized by TEM ( Figure 5 ), where no coating was observed along the edges, Figure 6 The EDS elemental mapping reveals the concentration distribution of V, Se, S, O, and C elements in the surface area of ​​the nanosheets, among which S, O, and C are the characteristic elements of PEDOT. The presence of these elements and their uniform aggregation in the coating area confirm the deposition of PEDOT on VSe2 nanosheets and further demonstrate the unparalleled super conformality exhibited by the MLD technology. Figure 7 X-ray diffraction (XRD) analysis of the electrode is presented. The XRD patterns of the electrode before and after coating have the same characteristics and the crystal structure does not change during the molecular layer deposition process, which is very consistent with the standard card PDF#89-1641 of VSe2.

[0050] S4: The VSe2 coated with 10 cycles of PEDOT obtained in S3 was directly used as the positive electrode, and the active material loading was 3 mg / cm 2 . A magnesium-lithium dual salt mixed electrolyte was prepared by dissolving 1M LiCl in a 0.4M tetrahydrofuran solution of PhMgCl-AlCl3. A glass fiber membrane (Whatman, GF / D) was used as a separator and a polished magnesium disc was used as a negative electrode. Button cells were assembled in an argon-filled glove box and electrochemical performance tests were performed at a current density of 200mA / g. Figure 8 As shown. After 200 charge and discharge cycles, the uncoated electrode maintained a considerable capacity of 137 mAh / g, while the coating increased the retention capacity to 172.9 mAh / g after 10 cycles, and the decay of the voltage curve was significantly suppressed. A long cycle test was then carried out, first activating it for three cycles with a current density of 50 mA / g, and then long cycling was carried out at a current density of 1 A / g, as shown. Fig. 9 As shown in the figure, the uncoated electrode maintained a considerable capacity of 64.3 mAh / g after 3000 charge and discharge cycles, while the capacity was increased to 107.3 mAh / g after 10 cycles of coating, reflecting excellent cycle stability. Fig.10The SEM image of the electrode after the medium cycle shows that the uncoated VSe2 sheet has a lot of peeling and severe cracking on the surface after 500 cycles at 1A / g, confirming that it suffered relatively serious mechanical damage during the cycle. In contrast, the VSe2 sheet coated with 10 cycles of PEDOT maintained its structural integrity well, without serious fractures and layer delamination, indicating that under the protection of the viscoelastic PEDOT coating, the stress of VSe2 is relieved during the cycle and it has enhanced mechanical properties, which is an important reason for the further improvement of electrochemical performance.

[0051] Example 2

[0052] S1: Preparation of carbon nanotube membrane current collector by vacuum filtration method: Pour 35 mg of multi-walled carbon nanotubes into 200 ml of N-methylpyrrolidone and ultrasonically treat for 6 hours to obtain a fully dispersed multi-walled carbon nanotube suspension, then vacuum filter to obtain a carbon nanotube membrane sheet, and finally put it in a forced air drying oven at 80°C and dry it for 24 hours to obtain a carbon nanotube membrane current collector.

[0053] S2: Growth of VSe2 nanosheets by atmospheric pressure chemical vapor deposition: Using a two-zone tubular furnace with separate temperature control, 0.1g of VCl3 powder, 0.5g of Se powder, and a carbon nanotube film current collector are placed on a quartz plate (boat). The Se powder is placed in the middle of the upstream temperature zone, the VCl3 powder is placed between the upstream and downstream temperature zones, and the carbon nanotube film current collector is placed ~2cm downstream of the VCl3. Before heating, a 95% N2+5% H2 mixed carrier gas is used for purging with a flow rate of 200-300sccm. At this time, the chamber double temperature zone is raised from room temperature to 120°C within 10 minutes and maintained for 20 minutes to create a preferred growth atmosphere. Then the carrier gas flow rate was reduced to 50 sccm. At the same time, the upstream temperature zone and the downstream temperature zone were heated to 370°C and 600°C at a heating rate of 5°C / min and 10°C / min respectively and maintained for 20 minutes. The furnace was then allowed to enter a natural cooling process, and finally a VSe2 integrated electrode directly grown on the carbon nanotube film current collector was obtained.

[0054] S3: Molecular layer deposition of PEDOT coating: The grown electrode is transferred to the molecular layer deposition reaction chamber, the chamber is heated to 150°C, MoCl5 powder is used as the oxidant, EDOT is used as the reaction monomer, and is placed in a source bottle to supply the precursor. The temperatures of the two source bottles are maintained at 200°C and 120°C respectively, thereby maintaining the high vapor pressure of the two precursors to obtain a sufficient supply of precursors. The chamber's base pressure is ~600mtorr, using nitrogen as the carrier gas (150sccm). The cyclic process of molecular layer deposition of PEDOT includes ~1s EDOT pulse + ~100s nitrogen pulse + ~5s MoCl5 pulse + ~100s nitrogen pulse, and 20 cycles of deposition are performed, through Fig.11 TEM images confirmed that a 10 nm coating layer was obtained.

[0055] S4: The VSe2 coated with 20 cycles of PEDOT obtained in S3 was directly used as an integrated electrode, with an active material loading of 3 mg / cm 2 . A magnesium-lithium dual salt mixed electrolyte was prepared by dissolving 1M LiCl in a 0.4M tetrahydrofuran solution of PhMgCl-AlCl3. A glass fiber membrane (Whatman, GF / D) was used as a separator and a polished magnesium disc was used as a negative electrode. Button cells were assembled in an argon-filled glove box and electrochemical performance tests were performed at a current density of 200mA / g. Fig.12 After 20 cycles of coating, the storage capacity increased to 148.8 mAh / g, still showing improved cycle stability.

[0056] Example 3

[0057] S1: Preparation of carbon nanotube membrane current collector by vacuum filtration method: Pour 35 mg of multi-walled carbon nanotubes into 200 ml of water and ultrasonically disperse for 6 hours to obtain a fully dispersed multi-walled carbon nanotube suspension, then vacuum filter to obtain a carbon nanotube membrane sheet, and finally put it into a forced air drying oven at 120°C and dry it for 24 hours to obtain a carbon nanotube membrane current collector.

[0058] S2: atmospheric pressure chemical vapor deposition growth of VSe2 nanosheets: using a two-zone tubular furnace with separate temperature control, 0.2g VCl3 powder, 2g Se powder, and carbon nanotube film current collector are placed on a quartz plate (boat). Se powder is placed in the middle of the upstream temperature zone, VCl3 powder is placed between the upstream temperature zone and the downstream temperature zone, and the carbon nanotube film current collector is placed at 5cm downstream of VCl3. Before heating, 95% N2 + 5% H2 mixed carrier gas is used for purging with a flow rate of 200sccm. At this time, the chamber double temperature zone is raised from room temperature to 120°C within 10 minutes and maintained for 30min to create a preferred growth atmosphere. Subsequently, the carrier gas flow rate is reduced to 60sccm. At the same time, the upstream temperature zone and the downstream temperature zone are heated to 370°C and 600°C at a heating rate of 5°C / min and 10°C / min, respectively, and maintained for 30 minutes. Then the furnace is allowed to enter a natural cooling process, and finally a VSe2 integrated electrode directly grown on the carbon nanotube film current collector is obtained.

[0059] S3: Molecular layer deposition of PEDOT coating: The grown electrode is transferred to the molecular layer deposition reaction chamber, the chamber is heated to 150°C, MoCl5 powder is used as an oxidant, EDOT is used as a reaction monomer, and is placed in a source bottle to supply the precursor. The two source bottles are maintained at 180°C and 100°C respectively, thereby maintaining a high vapor pressure of the two precursors to obtain a sufficient supply of precursors. The chamber's base pressure is ~600mtorr, using nitrogen as a carrier gas (150sccm). The molecular layer deposition of PEDOT includes a cyclic process of ~1s EDOT pulse + ~100s nitrogen pulse + ~5s MoCl5 pulse + ~100s nitrogen pulse, and 10 cycles of deposition are performed to obtain a 5nm coating layer.

[0060] S4: The VSe2 coated with 10 cycles of PEDOT obtained in S3 was directly used as an integrated electrode, with an active material loading of 5 mg / cm 2 . A magnesium-lithium dual salt mixed electrolyte was prepared by dissolving 1M LiCl in a 0.4M tetrahydrofuran solution of PhMgCl-AlCl3. A glass fiber membrane (Whatman, GF / D) was used as a separator and a polished magnesium disc was used as a negative electrode. Button cells were assembled in an argon-filled glove box and electrochemical performance tests were performed at a current density of 200mA / g. Fig.13 After 10 cycles of coating, the retention capacity increased to 103.8 mAh / g, indicating that despite the high active material loading, the molecular layer deposited 5 nm PEDOT coating combined with the self-supporting VSe2 electrode can still show significantly improved cycling stability.

[0061] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A method for preparing a VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating, characterized in that: The following steps are involved: S1: Preparation of carbon nanotube film current collector by vacuum filtration method: Multi-walled carbon nanotubes are added to a solvent and ultrasonically treated to obtain a fully dispersed multi-walled carbon nanotube suspension, and then vacuum filtered to obtain a carbon nanotube film sheet, which is then dried to obtain a carbon nanotube film current collector; S2: VSe2 flakes grown by atmospheric pressure chemical vapor deposition: using a two-zone tubular furnace with separate temperature control, Se powder is placed in the upstream temperature zone, VCl3 powder is placed between the upstream and downstream temperature zones, and the carbon nanotube film current collector is placed downstream of the VCl3 powder. In an inert atmosphere with a certain amount of carrier gas, the upstream and downstream temperature zones are heated to 350-370°C and 600-650°C respectively and maintained for a certain period of time, followed by natural cooling, and finally a VSe2 integrated electrode directly grown on the surface of the carbon nanotube film current collector is obtained. S3: Molecular layer deposition of PEDOT coating: On the surface of the integrated electrode prepared in step S2, EDOT monomer and oxidant are repeatedly and alternately pulse-sprayed and deposited to obtain a VSe2 self-supporting structure integrated electrode coated with a PEDOT coating.

2. The method for preparing the VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating according to claim 1, characterized in that: In the step S1, the solvent is at least one of N-methylpyrrolidone, water and ethanol.

3. The method for preparing the VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating according to claim 1, characterized in that: In the step S1, the concentration of the multi-walled carbon nanotubes in the solvent is 0.1-0.2 mg / mL.

4. The method for preparing the VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating according to claim 1, characterized in that: In step S1, the drying temperature is 80-120°C.

5. The method for preparing the VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating according to claim 1, characterized in that: In the step S2, the mass ratio of VCl3 powder to Se powder is 1:5-10.

6. The method for preparing the VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating according to claim 1, characterized in that: In the step S2, the carbon nanotube film current collector is placed 2-5 cm downstream of the VCl3 powder.

7. The method for preparing the VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating according to claim 1, characterized in that: The step S2 also includes a cleaning process of the chamber, and the specific steps are: before heating, a mixed carrier gas of 95% N2+5% H2 with a flow rate of 200-300sccm is used for purging. At this time, the double temperature zone of the chamber is raised from room temperature to 120-150°C within 10 minutes, and maintained for 20-30 minutes. Then, the carrier gas flow rate is reduced to 50-60sccm, and the temperature is raised for reaction. The growth time is 10-30 minutes.

8. The method for preparing the VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating according to claim 1, characterized in that: In step S3, the oxidant is at least one of MoCl5, ReCl5, and SbCl5, the heating temperature of the oxidant is 180-200°C, the pulse pressure is 1-3Pa, the heating temperature of the EDOT monomer is 100-120°C, the pulse pressure is 5-10Pa, and the deposition temperature is 130-160°C.

9. A VSe2 self-supporting structure electrode coated with an ultra-thin conformal PEDOT coating, characterized in that: The method according to any one of claims 1 to 8 is adopted to prepare the present invention.

10. Application of the VSe2 self-supporting structure electrode coated with the ultra-thin conformal PEDOT coating as claimed in claim 9 as a positive electrode material in a magnesium-lithium hybrid battery.

Citation Information

Patent Citations

  • Semiconductor device

    CN106972055A

  • Aqueous zinc-manganese battery fiber with dual-function protective layer and of fiber

    CN113036096A

  • Preparation method of self-supporting electrode with in-situ growth of bimetallic chalcogenide catalyst on surface

    CN118326426A

  • Organic / inorganic hybrid electrode, and secondary battery using the same

    JP2005285376A